Implied Warranty, Products Liability, and the Boundary Between Contract and Tort - Jay M. Feinman (Washington University Law Quarterly, 1997)
An unusual type of products liability case raises the issue of whether an injured consumer can recover for breach of an implied warranty of merchantability under the Uniform Commercial Code when the product that causes the injury is not defective under the tort rules governing products liability. Only a small number of cases fit this pattern, because in the overwhelming majority of cases a product that is unmerchantable-that is, not fit for the ordinary purposes for which it is used-will also be "in a defective condition unreasonably dangerous," to use the widely followed language of section 402A of the Restatement (Second) of Torts. Nevertheless, this type of case illuminates the nature of liability in implied warranty and in products liability, the relationship between the two, the broader relationship between contract law and tort law, the wisdom of portions of the proposed Restatement (Third) of Torts: Products Liability and of the proposed revision of Article 2 of the Uniform Commercial Code, and the current politics of the legal process.
Keywords: Product liability